DISPENSASI KAWIN OLEH PENGADILAN AGAMA DALAM PERSPEKTIF PERLINDUNGAN ANAK DI INDONESIA: ANALISIS KETEGANGAN ANTARA KEPASTIAN HUKUM, HUKUM PROGRESIF, DAN REALITAS SOSIAL - Raden Naila Nadira Mahali Soerianegara; Fitria Agustin (Jurnal Riset Multidisiplin Edukasi, 2026)
Marriage in the Indonesian legal system has juridical, religious, and social dimensions. The amendment of the minimum age of marriage under Law Number 16 of 2019, which sets the minimum age at 19 years, reflects a stronger orientation toward child protection. However, the existence of the marriage dispensation mechanism creates tension between legal certainty, justice, and expediency as conceptualized in Gustav Radbruch’s legal theory. This study employs a normative approach to analyze marriage dispensation from the perspectives of progressive law, legal protection, and the principle of the best interest of the child. The findings indicate that judicial discretion in granting marriage dispensation is influenced by social, economic, and cultural factors, thereby potentially shifting dispensation from an exceptional measure to a more commonly applied mechanism. This condition is further exacerbated by normative disharmony between marriage regulations and child protection laws, resulting in suboptimal protection of children in judicial practice.